An ADaptivE PrenaTal (ADEPT) intervention to increase childhood vaccinations: Protocol for a cluster randomized trial and nested mixed methods evaluation. - Lavanya Vasudevan; Rachael M Porter; Ilse Campos; Elizabeth L Turner; Sandra S Stinnett; Leah L Zullig; Emmanuel B Walter; Geeta K Swamy; Robert A Bednarczyk; Walter A Orenstein; Beverly Gray (PLoS ONE, 2024)
Background There is limited evidence to assess if interventions implemented during pregnancy proactively mitigate parental vaccine hesitancy and promote timely vaccination among children after birth. This study protocol describes the evaluation of an ADaptivE PrenaTal (ADEPT) intervention to increase childhood vaccinations that is implemented with first-time pregnant individuals (PIs). Methods Within the framework of a type 1 effectiveness-implementation hybrid study design, a cluster-randomized trial (CRT) will determine the effectiveness of ADEPT at increasing childhood vaccinations, and a nested explanatory mixed methods (NMM) study will assess changes in parental vaccine hesitancy. Study practices will be randomized to deliver ADEPT in addition to standard of care or standard of care alone. Providers at intervention sites will participate in a 4-part training program on childhood vaccines and effective communication. During a routine prenatal visit, providers will discuss vaccines recommended for the PI during pregnancy and for the child after birth, following which PIs will be screened for vaccination intention. Vaccine-hesitant PIs will be offered adaptive components of the intervention, which include an educational website and phone call with a vaccine navigator to discuss concerns. They will also be offered enrollment into the NMM study, where their vaccination intention will be assessed post-intervention. After PIs give birth, their child's vaccination outcomes at 2 months will be extracted from the state immunization registry. The primary study outcome is the difference in timely childhood vaccination at 2 months between the intervention and control arms. The secondary outcome is reduction in vaccine hesitancy assessed among PIs in the NMM study as the pre-post intervention change in vaccination intention. Discussion The study findings are expected to contribute evidence on the effectiveness of prenatal interventions to proactively mitigate parental vaccine hesitancy and promote timely vaccinations after the child's birth. Trial registration The study protocol is registered in ClinicalTrials.gov (NCT05795855).